Meeting the challenge : 1999 nuclear congress. (ICE Publishing, 1999)
This is the delegate pack for the 1999 BNES/BNIF nuclear congress.
Keywords: Nuclear engineering.; Nuclear engineering -- Great Britain.; Nuclear energy.; Nuclear energy -- Great Britain.; elektronické knihy; electronic books